Imam al-Syafi’i’s Thoughts about Ḥadīth and His Nāṣir al-Sunnah’s Title - Amelia Damayanti; Muhid Muhid (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2022)
Muhammad ibn Idris al-Syafi’i (w. 204 H) is a mujtahid imam, founder of the Syafi’i madzhab, which is spread throughout the world and whose madzhab include the majority madzhab in Indonesia. In addition to being one of the madzāhib al-‘arba’ah figure and pioneer of uṣūl al-fiqh sciences, Imam al-Syafi’i is also known as muḥaddits with his extraordinary thoughts to defend the ḥadīts of the Rasulullah Saw. To find out how Imam al-Syafi’i’s thoughts about ḥadīts, the author uses qualitative research metods and library research types. This research aims to find out how Imam al-Syafi’i’s thoughts about hadith. Furthermore, the author also describes the contributions that have been given by Imam al-Syafi’I until he obtained the title of Nāṣir al-Sunnah. The result of the research is Imam al-Syafi’i’s thoughts about ḥadīth that he was written in several his works. He set the criteria in the field of ḥadīth scince with a careful attitude. This is to avoid fabrication the narration of the Prophet’s ḥadīts so that its authenticity is maintained. His enthusiasm in upholding ḥadīts from several groups who reject ḥadīts as a source of Islamic law after the holy al-Qur’an, creating phenomenal works among Muslims, he has all tried to open the minds of the zindiq to hadith Rasulullah Saw. With various efforts and hard work assigned by Imam al-Syafi’i, the muslims pinned the title to him as Nāṣir al-Sunnah.